Rare Columnar Cell Variant of Papillary Thyroid Carcinoma with Cervical Spine Metastasis: A Case Report - Yu, Jihye; Yang, Goeun; Oh, Ha Yeun; Ryu, Yoon Jong (Current Medical Imaging, 2024)
BackgroundColumnar cell carcinoma is a rare subtype of papillary thyroid carcinoma (CCV-PTC) that accounts for only 0.15% to 0.2% of all Papillary Thyroid Carcinomas (PTCs). It has aggressive behavior but a better prognosis than anaplastic thyroid carcinoma.Case PresentationA 64-year-old female presented with a huge thyroid mass resulting in compressive myelopathy and was diagnosed as CCV-PTC, not anaplastic carcinoma. After multidisciplinary discussions, we decided to proceed with otolaryngological, thoracic, and orthopaedic surgery. All tumours were unresectable, and we planned to proceed with R2 resection to resolve the gait disturbance and anterior fusion to resolve spinal instability.ConclusionAdvanced-stage thyroid cancer is relatively uncommon, but desirable treatment effects can be expected through accurate pathological diagnosis. Immunohistochemical staining and tissue-specific markers can be helpful.
Keywords: Thyroid gland